ANALISIS STRUKTUR FUNGSIONAL PADA PERIBAHASA INDONESIA KARYA EKA MURTI SARI - Sri Juniati (STKIP Paris Barantai, 2021)
objectives of this study are (1) To describe the functional structure of Indonesian proverbs. (2) To describe wording patterns found in Indonesian proverbs. method used is qualitative descriptive method, method that describes or explains the research subject. object of research functional structure of Indonesian proverbs. object of research in this thesis is functional structure of Indonesian proverbs. Sources of data in study proverb books by Eka Murti Sari, data collection techniques means of library techniques, listening techniques and note taking techniques. The results showed that functional structure in the proverb was found in a complete patterned functional structure, namely; SP, SPO, SPK, SPPel, SPPelK, PS, PSK, SKP, KSP, Pel SP. functional structure with an incomplete pattern.functional structure has more than one pattern; SP / SP, SP / SP / SP, SP / SP / SP / SP, SP / SPK, SP / SPPel, SP / SKP, SP / Pel SP, SPO / SPO, SPK / SP, SPK / SPK, SPK / PK , SPPel / SP, SPPel / SPK, SPPel / SPPel, SPPel / SPPel / SPPel / SPPel, SKP / SP, SK / SK, SKP / SKP, PSK / PSK, PK / SP. Keywords: Functional Structure in Indonesian Proverbs